Investigation of the effects of different injection methods on the performance and emission characteristics of dual-fuel diesel engine fueled with diesel-ammonia mixtures - Kocatepe, Onur; Gonca, Guven (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
This study investigates the effects of different injection strategies on the performance and emission characteristics of diesel-ammonia dual-fuel engines using computational fluid dynamics (CFD) simulations. Two primary injection methods were analyzed: co-injection and post-injection strategies across varying ammonia energy ratios (10-50%). Results demonstrate that injection strategy significantly influences combustion efficiency, NOx formation, and unburned ammonia emissions. The co-injection method achieved superior thermal efficiency with maximum values of 38.46% at 50% ammonia ratio, while the post-injection strategy showed better emission control with reduced NH3 slip. NOx emissions decreased by up to 83.1% compared to pure diesel operation for post-injection and 58.5% for co-injection, while CO2 emissions reduced by 50.6% with co-injection and 40.2% with post-injection. This research provides critical insights for the development of environmentally sustainable diesel engine systems and contributes to the growing body of knowledge on carbon-free alternative fuels for internal combustion engine applications.
Keywords: Ammonia; Dual-fuel engine; Injection strategies; CFD simulation; Diesel engine; Emission reduction; COMBUSTION CHARACTERISTICS; EXERGY ANALYSES; CHEMISTRY; MECHANISM; HYDROGEN; ENERGY; Electrochemistry; Energy & Fuels